PENGARUH ROE TERHADAP CAR PADA LAPORAN KEUANGAN BANK MUAMALAT Tahun 2018-2022 - Anisa Putri Lestari; Aprilia Dewi Putri, Ayuni Maisiroh, Danang Arianto, Ria Saputri Liana, Nurhafiani (Adisam Publisher, 2024)
The importance of analyzing the influence of Return on Equity (ROE) on the Capital Adequacy Ratio (CAR) in Bank Muamalat's financial statements. ROE and CAR are two vital financial performance indicators in evaluating the efficiency of capital use and bank capital adequacy. By understanding the relationship between ROE and CAR, it can help banks optimize financial performance and maintain financial stability. This research aims to analyze the influence of Return on Equity (ROE) on the Capital Adequacy Ratio (CAR) in Bank Muamalat's financial reports in the 2018-2022 period. . The method used is panel regression analysis using secondary data from Bank Muamalat's financial reports. The ROE variable is used as the independent variable while CAR is the dependent variable. The research results show that there is a positive and significant influence between ROE and CAR at Bank Muamalat during the period studied. The implications of this research provide a better understanding of the relationship between financial performance and the level of capital adequacy of Islamic banks, especially Bank Muamalat, which can be a basis for decision making for related parties in risk management and business strategy in the future.